Impacts of Global Climate Change on the Future Ocean Wave Power Potential: A Case Study from the Indian Ocean - Harshinie Karunarathna (Energies, 2020)
This study investigates the impacts of global climate change on the future wave power potential, taking Sri Lanka as a case study from the northern Indian Ocean. The geographical location of Sri Lanka, which receives long-distance swell waves generated in the Southern Indian Ocean, favors wave energy-harvesting. Waves projected by a numerical wave model developed using Simulating Waves Nearshore Waves (SWAN) wave model, which is forced by atmospheric forcings generated by an Atmospheric Global Climate Model (AGCM) within two time slices that represent “present” and “future” (end of century) wave climates, are used to evaluate and compare present and future wave power potential around Sri Lanka. The results reveal that there will be a 12–20% reduction in average available wave power along the south-west and south-east coasts of Sri Lanka in future. This reduction is due mainly to changes to the tropical south-west monsoon system because of global climate change. The available wave power resource attributed to swell wave component remains largely unchanged. Although a detailed analysis of monthly and annual average wave power under both “present” and “future” climates reveals a strong seasonal and some degree of inter-annual variability of wave power, a notable decadal-scale trend of variability is not visible during the simulated 25-year periods. Finally, the results reveal that the wave power attributed to swell waves are very stable over the long term.